2002
DOI: 10.1200/jco.2002.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Goserelin Versus Cyclophosphamide, Methotrexate, and Fluorouracil as Adjuvant Therapy in Premenopausal Patients With Node-Positive Breast Cancer: The Zoladex Early Breast Cancer Research Association Study

Abstract: Goserelin offers an effective, well-tolerated alternative to CMF in premenopausal patients with ER-positive and node-positive early breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
166
1
18

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(193 citation statements)
references
References 20 publications
8
166
1
18
Order By: Relevance
“…2a), the best cut-off points of dichotomized evaluation of ER and PR positivity were more than 10% positive nuclei (F score>1). Dichotomized ER and PR expression was also highly associated with favorable DFS and OS in the present study, which provides evidence to support the criteria commonly used in clinical practice and some clinical trials in the adjuvant setting (Ellis et al, 2001;Jonat et al, 2002;Thurlimann et al, 2005).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…2a), the best cut-off points of dichotomized evaluation of ER and PR positivity were more than 10% positive nuclei (F score>1). Dichotomized ER and PR expression was also highly associated with favorable DFS and OS in the present study, which provides evidence to support the criteria commonly used in clinical practice and some clinical trials in the adjuvant setting (Ellis et al, 2001;Jonat et al, 2002;Thurlimann et al, 2005).…”
Section: Discussionsupporting
confidence: 69%
“…Using a definition of positivity as the presence of any level of staining by IHC, the Early Breast Cancer Trialists' Collaborative Group (EBCTCG, 2005) showed in a meta-analysis that tamoxifen significantly improved the prognosis of patients with ER positive tumors. However, in clinical practice and in some clinical trials, a cut-off of ≥10% ER and/or PR positive nuclei is often used for determining that a tumor is hormone receptor-positive and should be treated with adjuvant hormonal therapy (Ellis et al, 2001;Jonat et al, 2002;Thurlimann et al, 2005). The commonly applied 10% cut-off was established by Pertschuk et al (1996) who demonstrated a response to treatment in patients with metastatic breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In a large study comparing Sonmezer,Oktay 425 www.TheOncologist.com the efficacy and tolerability of monthly goserelin treatment for 2 years (n = 817) with CMF (n = 823), goserelin produced a similar DFS to that seen with CMF in estrogen receptor-positive patients after a median follow-up of 6 years [55]. In contrast, goserelin was found to be inferior to CMF in estrogen receptor-negative patients.…”
Section: Use Of Nongonadotoxic Ovarian Suppression Regimens As Adjuvamentioning
confidence: 88%
“…RT was found to compare unfavorably with the use of goserelin, in which amenorrhea was noted in 95% of patients at 6 months, and only somewhat more favorably than the amenorrhea rate of 58.6% noted at 6 months with the use of polychemotherapy. 13 In that same study, amenorrhea persisted at 3 years in 22.6% and 76.9%, respectively, of patients treated with goserelin and CMF. These data imply that in cases in which the reliability and reversibility of ovarian ablation are important, luteinizing hormone-releasing analogs may be a more advantageous choice than RT.…”
Section: Discussionmentioning
confidence: 80%